Loratadine bioavailability via buccal transferosomal gel: formulation, statistical optimization, in vitro/in vivo characterization, and pharmacokinetics in human volunteers - Mohammed H. Elkomy; Shahira F. El Menshawe; Heba A. Abou-Taleb; Marwa H. Elkarmalawy (Taylor & Francis Group, 2017)
Loratadine (LTD) is an antihistaminic drug that suffers limited solubility, poor oral bioavailability (owing to extensive first-pass metabolism), and highly variable oral absorption. This study was undertaken to develop and statistically optimize transfersomal gel for transbuccal delivery of LTD. Transfersomes bearing LTD were prepared by conventional thin film hydration method and optimized using sequential Quality-by-Design approach that involved Placket-Burman design for screening followed by constrained simplex-centroid design for optimization of a Tween-80/Span-60/Span-80 mixture. The transferosomes were characterized for entrapment efficiency, particle size, and shape. Optimized transferosomes were incorporated in a mucoadhesive gel. The gel was characterized for rheology, ex vivo permeation across chicken pouch buccal mucosa, in vitro release, and mucoadhesion. Pharmacokinetic behavior of LTD formulations was investigated in healthy volunteers following administration of a single 10-mg dose. Optimal transferosomes characterized by submicron size (380 nm), spherical shape and adequate loading capacity (60%) were obtained by using quasi-equal ratio surfactant mixture. In terms of amount permeated, percentage released, and mucoadhesion time, the transferosomal gel proved superior to control, transferosome-free gel. Bioavailability of the transferosomal gel was comparable to Claritin® oral tablets. However, inter-individual variability in Cmax and AUC was reduced by 76 and 90%, respectively, when the buccal gel was used. Linear Correlation of in vitro release with in vivo buccal absorption fractions was established with excellent correlation coefficient (R2>0.97). In summary, a novel buccal delivery system for LTD was developed. However, further clinical investigation is warranted to evaluate its therapeutic effectiveness and utility.